Investigating significant health trends in idiopathic pulmonary fibrosis (INSIGHTS-IPF): rationale, aims and design of a nationwide prospective registry - Behr, Jürgen; Hoeper, Marius M.; Kreuter, Michael; Klotsche, Jens; Wirtz, Hubert; Pittrow, David (BMJ Open Respiratory Research, 2014)
Guidelines on the diagnosis and management of idiopathic pulmonary fibrosis (IPF), a rare manifestation of chronic progressive fibrosing interstitial pneumonia, have been updated by ATS/ERS/JRS/ALAT in 2011. In Europe, data are limited on the characteristics and management of such patients.